Course of posttraumatic stress disorder following war in the Balkans : one-year follow-up study - Priebe, Stefan (Array, 2013)
Background Prevalence rates of Post-Traumatic Stress Disorder (PTSD) following the experience of war have been shown to be high. However, little is known about the course of the disorder in people who stayed in the area of conflict and in refugees. Methods We studied a representative sample of 522 adults with war-related PTSD in five Balkan countries, and 215 compatriot refugees in three Western European countries who were recruited through registers and networking. They were assessed on average eight years after the war and re-interviewed one year later. We established change in PTSD symptoms (assessed on the Impact of Events Scale – Revised ; IES-R) and factors associated with better outcomes. Results During the one year period, symptoms decreased substantially in Balkan residents and in refugees. The differences were significant for IES-R total scores and for the three subscales of intrusions, avoidance and hyperarousal. In multivariable regressions adjusting for the level of baseline symptoms, co-morbidity with depression predicted less favourable symptom change in Balkan residents. More pre-war traumatic events and the use of mental health services within the follow up period were associated with less improvement in refugees. Conclusions Several years after the war, people with PTSD reported significant symptom improvement which might indicate a fluctuating course over time. Co-morbid depression may have to be targeted in treatment of people who stayed in the war region, whilst using mental health services appears to be linked to the persistence of symptoms amongst refugees.